ТАЛАБАЛАР БИЛИМИНИ БАҲОЛАШНИНГ МАҚСАДИ ВА ВАЗИФАЛАРИ - Ашурова, Ф.Л. (SCIENCE and SOCIETY, 2019)
In the article the author discusses some ideas and opinions about assessment criterions for EFL as an academic subject, especially in such subjects as Reading and Writing for the first year students. The article reflects some new approaches for assessment of learners’ outcomes.